Phycolimnological study of some wastewater of Sulaimani Provience -Kurdistan Region of Iraq - Ahmed, Dalya S.; Farkha, Trifa K. (Sulaimani Journal for Pure and Applied Sciences, 2020)
This work is aimed to study the characteristics of some wastewater in Sulaimani city. Water samples were collected monthly from October 2018 to May 2019 from four sites, two of them Site1:Tanjaro River before bridge,Site 2:Tanjaro River after bridge along Tanjaro river , Site3:kana swra and Site4:Awbara from weast water of Sulaimani city box channels which finally flow into Tanjaro river . To represent their water quality some physical , chemical and Biological analysis were conducted. The mean value of pH for all studied sites was found to be above 7 . The value of Electrical conductivity(EC) in Sites 1,2,3 and 4 were ranged between(407-601 µs/cm),( 266-585 µs/cm) ,( 773-1004 µs/cm) and(398-975 µs/cm)respectively, Turbidity ranged between(42-1001 NTU),( 57-986 NTU),( 32-1010.5 NTU) and(41-643 NTU) in Site 1,2,3 and 4 respectivly and Chemical Oxygen Demand (COD) value in Site 1,2,3 and 4 were ranged between(251-975.5 mg/L),( 275-926 mg/L),( 354-1025 mg/L) and(452-1025 mg/L) respectively. A total of 114 algal taxa were identified belonging to 7 classes, 63 taxa belonged to Bacillariophyceae species, they were the most abundant group (4 taxa belong to centrales and 59 taxa belonging to pinnales), followed by 24 taxa of Cyanophyceae ,22 taxa chlorophyceae, , 2 taxa Pyrophyceae and 1 taxa for each of Euglenophyceae , Rhodophyceae and Xanthophyceae. Higher phytoplankton density was recorded in Awbara (58269.44ind×103/L), while the lowest density was recorded in Tanjaro River after the bridge which was (14300.2ind×103/L) .
Keywords: Physicochemical parameters; Wastewaters; Tanjaro River; phytoplankton